Topic Continuity in Song Lyrics: A Quantitative Discourse Analysis of “Perfect” by Simple Plan - Deliana, Deliana; Simanjuntak, Ivan Fernando; Ilma, Dzikri (Indonesian Journal of Advanced Research, 2025)
This study investigates topic continuity and referential cohesion in the song “Perfect” by Simple Plan using Givón’s quantitative model. The objective is to analyze how various types of anaphoric references, including zero anaphora, definite pronouns, third-person pronouns, and possessive pronouns, function to maintain coherence and convey emotional meaning within the lyrics. Employing a qualitative descriptive design supported by quantitative analysis, the research examines the referential distance (JR), potential interference (PI), and topic continuity (TC) in each clause of the song. The data consist of all anaphoric expressions identified in the lyrics, collected through close reading and clause segmentation. The findings reveal that the song heavily relies on first and second person pronouns to construct an intimate and emotionally charged discourse. Zero anaphora is used selectively to create immediacy, while third-person and possessive pronouns support abstract and personal references. The absence of indefinite pronouns reflects the song’s focus on specific interpersonal conflict. These results suggest that Givón’s model is applicable to expressive, non-traditional texts such as song lyrics. The study contributes to the field of stylistics and discourse analysis by demonstrating how referential cohesion shapes meaning in emotionally driven narratives.